Management of capital liquidity in public hospitals under the epidemic situation of COVID-19 - Hu, Xiaoqiao; Jin, Wei; Yang, Ailan; Hu, Zhigang (Frontiers in Public Health, 2022)
The epidemic of COVID-19 has a great impact on the life and safety of people around the world. As the main force in the fight against COVID-19, the financial management of public hospitals will provide a strong guarantee for the diagnosis and treatment behavior of medical staff. The financial department needs to recognize the extent of the impact of COVID-19 on hospital finance, quantify and predict the potential risk factors, and develop reasonable financial management strategies. As an important part of assessing the financial health of public hospitals, the capital liquidity can be used as the focus direction of the hospital managers. In this study, we determines the effects of COVID-19 on the finance of public hospitals. Subsequally, we invested the conception, components, risk factors of capital liquidity in public hospitals. In addition, we provided some management strategies of capital liquidity in public hospitals under the epidemic of COVID-19. We deemed that good capital liquidity can ensure that medical staff have enough confidence and mentality to face the risk of death from COVID-19.